2021
DOI: 10.2967/jnumed.121.262383
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Fc Modifications and IgG Subclass on Biodistribution of Humanized Antibodies Targeting L1CAM

Abstract: Immuno-positron emission tomography (immuno-PET) is a powerful tool to noninvasively characterize the in vivo biodistribution of engineered antibodies (Abs). Methods: L1 cell adhesion molecule (L1CAM)-targeting HuE71 immunoglobulin G1 (IgG1) and immunoglobulin G4 (IgG4) Abs bearing identical variable heavy and light chain sequences but different fragment crystallizable (Fc) portions were radiolabeled with Zirconium-89 ( 89 Zr) and the in vivo biodistribution was studied in SKOV3 ovarian cancer xenografted nude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…3 ). Interestingly, we observed lower liver uptake of click antibodies in immunocompetent mice (8.9±1.5 %ID/g) when compared with immunocompromised mice (4.5±2.4 %ID/g), as immunocompetent mice have circulating IgG ( 37, 38 ) ( Supplementary Fig. 4) .…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…3 ). Interestingly, we observed lower liver uptake of click antibodies in immunocompetent mice (8.9±1.5 %ID/g) when compared with immunocompromised mice (4.5±2.4 %ID/g), as immunocompetent mice have circulating IgG ( 37, 38 ) ( Supplementary Fig. 4) .…”
Section: Resultsmentioning
confidence: 76%
“…3 ). Antibody click in blood circulation likely enhances the interaction of the Fc domain of mAbs with Fc receptors in the liver of immunocompromised mice ( 37 ). Additional studies demonstrated that pre-injection of a 15-fold excess of cold IgG significantly lowered liver accumulation ( Extended Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, Sharma et al demonstrated the power of this approach using two glycoengineered variants of the L1CAM-targeting radioimmunoconjugate [ 89 Zr]Zr-DFO-HuE71 (Fig. 4B) (28). An afucosylated variant with enhanced FcgRIIIA binding exhibited reduced tumoral uptake and enhanced accretion in the liver and lymphoid tissues compared with the parent radioimmunoconjugate.…”
Section: Modulating Fc Interactionsmentioning
confidence: 99%
“…In the study from Sharma et al mentioned above, the authors also explored 89 Zr-immunoPET with two L1CAM-targeting IgG 4 -based radioimmunoconjugates, as this subclass has attracted attention in the immunotherapeutics community because it elicits reduced effector functions relative to other subclasses (Fig. 4D) (28). Although a radioimmunoconjugate based on the wild-type IgG 4 framework produced high levels of nonspecific uptake in the kidneys, this behavior was eliminated in a variant with S228P mutations in the hinge region that facilitated the formation of IgG 1 -like interchain disulfides and thus mitigated in vivo Fab arm exchange.…”
Section: Modulating Fc Interactionsmentioning
confidence: 99%